The Esthetic Difference of Chinese Beauty Evaluated by Two Different Human Races Based on Three-Dimensional Average Face Analysis. Issue 5 (July 2019) - Chen, Cong; Chen, Yutong; Li, Qingyi; Kau, Chung How
Abstract : Purpose: The aim of this study was to establish a new method of facial soft tissue analysis based on 3dMDface system and to find the different esthetic preferences of Chinese beauties from the Chinese and Indian evaluators perspective. Methods: Three-dimensional facial images of 242 females and 168 males were evaluated and ranked by 8 Chinese and nine Indians using a 10-point visual analog scale (VAS). Total 120 subjects in 2 panels (from Chinese perspective and Indian perspective) including 30 male and 30 female faces with top 30 scores were analyzed with the "average face" method respectively. Then 17 linear measurements, 13 curve measurements and 14 ratios of 4 average faces were calculated and compared with the divine proportion. Results: Distinct differences were founded based on the average face analysis. Similar total facial types were preferred by both Chinese and Indian evaluators, while Indian evaluators preferred a wider male face with a protrusive lower lip. Delicate noses with lower nose ridge but protrusive lower lips in females were more acceptable by Indian evaluators. The differences of linear measurements were limited in 2.0 mm except the facial width, lower facial width, upper facial height and forehead height while curve measurements differ distinctly as the table shows. No ratios equal to the divine proportion were founded. Conclusion: The 3D Average face based on stereophotogrammetry is a feasible method to analyze the facial characters and discrepancy of esthetic preferences. Chinese and Indian evaluators have some certain differences when judging beauties. Attractive faces have some certain ratios but not the divine proportion. Abstract : Supplemental Digital Content is available in the text